How to look good in a war : justifying and challenging state violence - Rappert, Brian (Pluto Press, 2012)
Examines the methods used to depict, defend, and justify the use of state violence, analyzing how pro-war narratives are constructed and normalized through studying government spin during recent wars in Iraq, Afghanistan, and Libya.